ANALISIS FENOMENOLOGI ALFRED SCHUTZ: TRADISI TAKBIR KELILING PONDOK PESANTREN KRAPYAK YAYASAN ALI MAKSUM YOGYAKARTA - Dzikrillah Alfani, Ilzam Hubby; Duwi Putri, Widia (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2024)
The tradition of traveling takbir at the Ali Maksum Foundation Krapyak Islamic Boarding School has become a routine every year in the month of Zulhijjah. During the activity, participants wore a variety of attractive clothing that brought Islamic and cultural elements. This research aims to explain the values contained in the clothing worn, because each clothing worn by each group of participants has messages to be conveyed to the audience or judge. The approach used in qualitative research is a literature study approach which refers to sources related to the research. The results of this research show that the clothing worn by each participant has a hidden meaning. For example, Muslim clothing depicts Santri as figures who are protected from all evil, batik clothing depicts the diversity of Santri in terms of race, ethnicity, culture, vision and mission. Surjan clothing symbolizes elegance. Not everyone can become a Santri, but everyone has the opportunity to become a Santri. Umaro’s clothing illustrates that Santri are future leaders. Jarik clothing depicts Santri as humble figures who are far from arrogant.